Sosialisasi dan Pendampingan Pengelolaan Kelompok Sadar Wisata di Desa Mekarbuana Kabupaten Karawang – Jawa Barat - Rinie Octaviany Hasan; Lala Siti Sahara; Jenal Abidin; Rahmat Darmawan (Nusantara Mengabdi Kepada Negeri, 2024)
Mekarbuana Village located in Tegalwaru, Karawang district, West Java, is about 45 kilometers from the center of Karawang, and has potential for agro-tourism and natural tourism, because according to the village head, Jaji Maryono, the village is a provider of coffee, durian, mango, avocado, and bananas. The tourism that are available are Curug Cigentis, Curug Bandung, and tours along the flow of the river. This tourist destination is a favourite destination of both locals and citizens around Karawang to spend the weekend with the family. Due to the tourist potential in his village, the village chief acknowledged that he wanted to bring Mekarbuana Village into a tourist village, but still needed support and enhanced human resource capacity (HRM) to manage the village. The problem is that the tourism organization in the village are not functioning, so the wheel of tourism in that village is still not balanced. This activity uses methods of accompaniment, socialization, and education carried out in integration with KKN students to the community and tourists in Mekarbuana Village. The result of this community service activity is the reactivation of the pokdarwis management, the existence of the organization structure, the presence of the work plan, a varied tour package, as well as the Mekarbuana Village already registered in the JADESTA. As to the conclusion of the activities, they feel very grateful and hoped that the organization will be able to maximize its management, and continue to run consistently and professionally in managing tourism in the village.